LGBT rights in a Republic of Therapy. HIV/AIDS policies and the redefinition of citizenship in Cameroon - (:unkn) unknown (My University, 2017)
The links between the fight against HIV/AIDS, and lesbian, gay, bisexual and transgender (LGBT) mobilizations around the world have been extensively demonstrated. However, there are few empirical studies on the effects of new strategies based on access to treatments for homosexuals in Africa, especially in countries where same-sex relationships are punishable by law. In discussing the relationship between HIV/AIDS policies and the formal recognition and inclusion of homosexuals, we ask if it is possible to speak of a therapeutic citizenship. From a sociological and legal perspective, what is important is how the recent global strategies and human rights discourses on HIV/AIDs are impacting the emergence of engaged social actors whose claims go well beyond access to treatments but challenge the Cameroonian legal and health systems. However, LGBT rights advocates’ claim for full citizenship through participatory inclusion in public life may not turn out to be successful as it encloses their rights within a pathologized identity, the HIV epidemic. This paper also raises a crucial issue (citizenship) associated with the politics of homosexuality in Africa and offers an empirical dimension on how global health and human rights discourses affect the relationship between State and society in Cameroon.
Keywords: African Research